2019
DOI: 10.1111/jne.12669
|View full text |Cite
|
Sign up to set email alerts
|

30 years after: CNS actions of prolactin: Sources, mechanisms and physiological significance

Abstract: Our understanding of the neural actions of prolactin (PRL) and its biochemical basis has expanded greatly over the past three decades. During this time, major progress has been made, including clarification of how PRL accesses the brain, identification of the PRL receptor and the sites where it is expressed within the brain, determination of the neurochemical mechanism of action of PRL and its effect on genomic expression in neurones, identification of the neural sites where PRL acts to stimulate maternal beha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 118 publications
(200 reference statements)
1
23
0
Order By: Relevance
“…In the central nervous system, prolactin participates in a coordinated neural network which prepares a maternal brain for pregnancy and lactation. It stimulates maternal care by acting within the medial preoptic area (MPOA), 35,36 modulates stress response and oxytocin secretion acting at the F I G U R E 2 Gene expression in the ARN of 5 and 10-month-old Drd2 LoxP/LoxP and lacDrd2KO mice. Genes were relativized to the housekeeping gene cyclophilin and the average expression of Drd2 LoxP/LoxP mice was considered 100%.…”
Section: Discussionmentioning
confidence: 99%
“…In the central nervous system, prolactin participates in a coordinated neural network which prepares a maternal brain for pregnancy and lactation. It stimulates maternal care by acting within the medial preoptic area (MPOA), 35,36 modulates stress response and oxytocin secretion acting at the F I G U R E 2 Gene expression in the ARN of 5 and 10-month-old Drd2 LoxP/LoxP and lacDrd2KO mice. Genes were relativized to the housekeeping gene cyclophilin and the average expression of Drd2 LoxP/LoxP mice was considered 100%.…”
Section: Discussionmentioning
confidence: 99%
“…The pattern of lamprey PRLR mRNA expression (high in the brain; moderate in the gill, kidney and gut) is opposite that of the pattern of PRLR mRNA expression in teleost (e.g., high in the osmoregulatory tissues, but less in the brain) 13,40 . Interestingly, shark PRLR is predominantly expressed in the pituitary gland with unknown function 5 and mammalian PRLR has wide distribution in the central nervous system and appears important for regulating parental behavior as well as appetite and food intake 42 . Lamprey PRLR may mediate similar roles in the brain of lampreys.…”
Section: Discussionmentioning
confidence: 99%
“…Given the critical role elevated prolactin levels play in mediating lactation and facilitating a wide range of associated maternal adaptations, it is not surprising that the TIDA neurones modify their physiology during this time. 18 It has, for example, been demonstrated that they markedly reduce their synthesis and release of dopamine during lactation, thus alleviating its inhibitory action on the lactotrophs. [19][20][21] By contrast to initial expectations, 19,20 this adaptation does not appear to result from a down-regulation of TIDA neurone responsiveness to prolactin.…”
Section: Introductionmentioning
confidence: 99%